Feedback in The Learning Process on Indonesian Master’s Degree Experience Studying Abroad - Muhammad Hidayat; Saleh, M Nurul Ikhsan (JTP - Jurnal Teknologi Pendidikan, 2022)
Studies on the perception of Indonesian master’s degree students from various universities abroad on satisfaction with feedback in the learning process are still limited. This study aims to explore the perceptions of college students related to feedback and how the feedback enables students to sharpen and improve practical skills in the learning process. Researchers in this study uses a case study method included in qualitative research. Researchers interviewed 32 participants who were selected using the snowball sampling technique which consisted of master degree students from four countries: Indonesia, the United Kingdom, the United States of America, and Australia. The questions in this study focused on responses to various types of feedback based on the question and delivery, student expectations, and how feedback affects academic performance. This study found four major themes, namely the importance of being explicit in providing feedback, variations in giving feedback, comprehensive feedback students expect for lecturers in Indonesia, and using feedback to improve students’ academic performance.